Effects of Live Yeast and Yeast Extracts with and without Pharmacological Levels of Zinc on Antimicrobial Susceptibilities of Fecal Escherichia coli in Nursery Pigs - Jenna A. Chance; Jordan T. Gebhardt; Joel M DeRouchey; Raghavendra G. Amachawadi; Victor Ishengoma; T. G. Nagaraja; Qing Kang; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joseph A. Loughmiller (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 360 weanling barrows (Line 200 × 400, DNA Genetics; initial BW 12.4 ± 0.05 lb) were used in a 42-d study to evaluate yeast-based pre- and probiotics (Phileo by Lesaffre, Milwaukee, WI) in diets with or without pharmacological levels of Zn on antimicrobial resistance (AMR) patterns of fecalEscherichia coli. Pens were assigned to 1 of 4 dietary treatments with 5 pigs per pen and 18 pens per treatment. Dietary treatments were arranged in a 2 × 2 factorial with main effects of live yeast-based pre- and probiotics (none vs. 0.10% ActiSafSc 47 HR+, 0.05% SafMannan, and 0.05% NucleoSaf from d 0 to 7, then concentrations were lowered by 50% from day 7 to 21) and pharmacological levels of Zn (110 vs. 3,000 ppm from d 0 to 7, and 2,000 ppm from d 7 to 21 provided by ZnO). All pigs were fed a common diet from d 21 to 42 post-weaning without live yeast-based pre- and probiotics or pharmacological Zn. Fecal samples were collected on d 4, 21, and 42 from the same three pigs per pen for fecalE. coliisolation. The identification ofE.coliwas by PCR detection ofuidAandclpBgenes. The AMR patterns of E. coli were determined by microbroth dilution method using Sensititre CMV3AGNF panel containing 14 different antimicrobials. The addition of pharmacological levels of Zn had a marginally significant effect (P= 0.051) to increase the minimum inhibitory concentration (MIC) values of ciprofloxacin; however, median MIC values were still under the Clinical and Laboratory Standards Institute (2018) classified resistant breakpoint for ciprofloxacin. There was no evidence for differences (P>0.05) for yeast additives or Zn for AMR of fecalE. coli isolates to any of the remaining antibiotics. In conclusion, pharmacological levels of Zn tended to increase the AMR of fecalE. colito ciprofloxacin while the medians were below a resistant breakpoint. There was no influence of live yeast and yeast extracts on AMR patterns of fecalE.coliagainst tested antimicrobials.
Keywords: nursery pigs; probiotics; yeast; yeast extracts; zinc